Derivative Analysis of Gravity Data in Revealing the Subsurface Fault Structure Model in Semeru Volcano, East Java and Its Surrounding - Hofi, Laily Nur; Maryanto, Sukir; Susilo, Adi; Wuryani, Sri Dwi (Trends in Sciences, 2024)
Research with gravity data in the area of Semeru volcano has been undertaken. The study aims to determine the subsurface fault structure of the Semeru volcano by utilizing derivative analysis of gravity data anomalies. A comprehensive dataset of 1,929 measurement points, spaced 500 m apart, was analyzed to identify variations in the Bouguer anomaly. Complete Bouguer anomaly values ranged from 37 to 111 mGal. The contrast of Bouguer anomaly variations effectively delineates the boundaries of different rock formations: Mandalika, Wuni, Quarter Volcanic Semeru and Quarter Volcanic Jembangan. These formations are instrumental in causing significant variations in gravity anomalies, indicating an underlying geological structure. The derivative analysis, encompassing horizontal (FHD) and vertical (SVD) anomalies, unveiled a pronounced fault structure southeast of the Semeru crater, characterized by a NE-SW orientation. Advanced modeling, informed by residual anomaly incision lines and depth estimates derived from the radial spectrum, revealed a complex subsurface stratigraphy consisting of 5 types: Volcanic clastics, tuff, breccia, basaltic lava and andesitic lava. This research advances our understanding of the Semeru volcano’s subsurface architecture. It introduces an enhanced methodology for fault detection and characterization in volcanic areas, showcasing the potential of gravity data in geological investigations. HIGHLIGHTS Gravity data processing: The research presents Bouguer anomaly which represents the subsurface geological formation of Semeru volcano. Estimating of fault structure based on derivative analysis of the gravity data from incision lines of anomaly map. Construction of geological subsurface, including rock formation boundaries and fault structures, in 2-dimensional models of gravity anomalies. GRAPHICAL ABSTRACT